Análise de cascas espessas com elementos finitos mistos - Fabris, Carlos Renato (1978)
This paper presents the development of a mixed finite element for analysis of thick shells of arbitrary shape, in the most general case. The fundamental unknowns are stresses and displacements. The analysis is linear and is based on the Theory of Elasticity. The finite element at issue is a degenerated quadratic tridimensional isoparametric, and takes into consideration the transverse shearing deformations. Listing of the ALGOL program is included in the appendix. The computer program treats shells, plate bending and plane stress problems, considering different kinds of loads and effects of temperature changes. The convergence behaviour of this element is analysed, among others, with regard to the influence of the number of integration points and of the prescribed boundary conditions.